ECONOMIC CAPACITY AND DEVELOPMENT PROSPECTS OF SMALL BUSINESS IN THE SERVICE SECTOR - Sultonov Shodiyor Аbduhаlilovich (THE INNOVATION ECONOMY, 2026)
This article analyzes the economic potential of small businesses in the service sector, their role in the development of the national economy, and the prospects for development in modern conditions. The service sector is an important factor in ensuring economic growth, creating new jobs, increasing the income of the population, and expanding entrepreneurial activity. The study examines the share of small business entities in the service market, their economic efficiency, opportunities for the introduction of innovative technologies, and the mechanisms of state support.